Penggunaan Effect Size Sebagai Mediasi dalam Koreksi Efek Suatu Penelitian - Khairunnisa Khairunnisa; Fenty Fitrian Sari; Mega Anggelena; Deka Agustina; Euis Nursa'adah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to examine studies on the use of effect size in estimating the effect size of an experiment in various fields of science. The method used is Literature Review by searching for relevant articles in the databases of Google Scholar, National Center or Biotechnology Information (NCBI), Mendeley and ScienceDirect. The results of the study indicate that overall the articles reviewed show the use of effect size as a statistical test to determine the effect size of treatment in research studies. However, in its use, the effect size needs to be included with other statistical tests to obtain a small refractive index so that the data is more accurate. In conclusion, the effect size is part of a statistical test that plays a role in helping users understand the magnitude of the differences found in a research experiment. Keywords: Accuracy, Effect Size, Experiment, Statistics